Application of Local Fractional Series Expansion Method to Solve Klein-Gordon Equations on Cantor Sets - Ai-Min Yang; Yu-Zhu Zhang; Carlo Cattani; Gong-Nan Xie; Mohammad Mehdi Rashidi; Yi-Jun Zhou; Xiao-Jun Yang (Abstract and Applied Analysis)
We use the local fractional series expansion method to solve the Klein-Gordon equations on Cantor sets within the local fractional derivatives. The analytical solutions within the nondifferential terms are discussed. The obtained results show the simplicity and efficiency of the present technique with application to the problems of the liner differential equations on Cantor sets.